Development Of High School Physics Practical Guidelines In Sound Resonance Instrument Using Model Learning Discovery Learning - Bayu Ritno Matialo; H. Taunaumang; Marianus; Cosmas Poluakan; Jovialine Albertine Rungkat (PT. AHLAL PUBLISHER NUSANTARA, 2026)
This research is motivated by the availability of new laboratory equipment assistance in the form of a Sound Resonance tool in 2024 at SMA Negeri 2 Kotamobagu which has not been optimally used due to the unavailability of specific practicum guidelines. This has an impact on the lack of direct experimental activities and low achievement of students' science process skills. This study aims to develop a product in the form of a high school Physics practicum guide on the Sound Resonance tool by integrating a valid and feasible Discovery Learning learning model. This type of research is Research and Development (R&D) by applying the 4-D development model (Define, Design, Develop, Disseminate). The trial subjects in this study were Grade XII students in the second semester of SMA Negeri 2 Kotamobagu in the 2025/2026 academic year. Data collection instruments include validator/material and media expert assessment sheets, student response sheets, and practicum performance observation sheets. The validation results by the expert team showed that the general design and completeness of the practicum guide were in the feasible category after going through several revisions to strengthen the concept. In the Develop stage through small group trials (10 students), the percentage of positive student responses reached an accumulation of 97.5%, with an average achievement of 83.75% of the practical task performance which is in the valid and feasible qualification. In the Disseminate stage through large-scale trials (20 students), the positive student responses increased to reach an accumulation of 100% in the very useful and beneficial category. Based on these results, it can be concluded that the Discovery Learning-based Physics practical guide on the Sound Resonance tool is declared valid, feasible, and effective to be used to optimize laboratory activities and meet the criteria for student completion in the cognitive, affective, and psychomotor aspects. Keywords:Practical Guide, Sound Resonance, Discovery Learning, 4-D Model, Physics Education.